Antenatal depression and its associated risk factors among males: evidence from an urban setting in a lower-middle income country: Antenatal depression among males - Atif, Maria (Journal of Pakistan Psychiatric Society, 2026)
Objective: To estimate the prevalence and associated risk factors of paternal antenatal depression among men attending urban healthcare settings in Karachi, Pakistan.Study Design: Cross-sectionalPlace and Duration of the study: This study was conducted at the Department of Obstetrics and Gynaecology, Dow University of Health Sciences and the Modern Sindh Government Hospital from November 2023 to April 2024.Method: The study population comprised adult males with pregnant wives attending the selected healthcare facilities for antenatal examinations. Participants’ information statements and consent forms were shared with eligible males, accompanying their pregnant wives for antenatal check-ups during the research period. Edinburgh Postnatal Depression Scale was utilized to assess antenatal depression among the participants.Results: A total of 312 males participated in this study. The prevalence of antenatal depression among expectant fathers was found to be 52%. This study found a very high prevalence of paternal antenatal depression among the sample, with the advanced paternal age, lower income levels, experiencing sleep disturbance and being a smoker among the significant risk factors of depression among expectant fathers. The results of the study help to explain why fathers should also be engaged in perinatal mental health interventions.Conclusions: This study identified prevalence of paternal antenatal depression among expectant fathers in Karachi. Significant risk factors included advanced paternal age, lower socioeconomic status, sleep disturbances, and smoking habits, indicating an urgent need for involving fathers in perinatal mental health programs, vital for promoting overall family well-being.